Mechanical response of high-porosity rocks under high triaxial confining pressure and experimental study of indentation tests - Jingming Gai; Wei Li (PLoS ONE, 2026)
As oil and gas exploration and development continue to advance, ultra-deep and extra-deep formations have become the primary battleground for increasing global oil and gas reserves and production. The influence of high formation pressure on the macro-mechanical response of rock, particularly the mechanical response of indentations, remains unclear. This paper takes high-porosity rocks, which are commonly found in ultra-deep and extra-deep formations, as the research object. True triaxial compression test(TTCT) and conventional triaxial compression tests(CTCT) were conducted on high-porosity red sandstone to analyze brittle-ductile transition characteristics. A high confining pressure indentation test apparatus was developed to investigate the mechanical response of spherical indentation under high confining pressure. Numerical simulations were employed to analyze the underlying mechanism of this mechanical response. The results indicate that as the confining pressure increases, the sample undergoes three failure modes: shear failure, dilatant failure, and compactive cataclastic flow. The peak points of the stress‒strain curves present two distinct failure surfaces on the p-q meridian plane, and the location of these failure surfaces on the p-q meridian plane largely determines the stiffness response of the indentation. The indentation stiffness does not always increase with the increase of confining pressure, but rather exhibits a significant reduction near the brittle-ductile transition point. The release of residual stress leads to significant side crack propagation during indenter unloading, but this phenomenon is significantly inhibited under confining pressure. This paper offers preliminary insights into the mechanical behavior of oil and gas drilling scenarios under high confining pressures, such as those in ultra-deep and extra-deep formations, and provides an initial understanding of the indentation mechanical response of high-porosity rocks under high confining pressure.